Anthropometric characteristics of ultramarathoners - Hoffmann, M. D. (International Journal of Sports Medicine, 2008)
Little is known about the anthropometric characteristics of ultramarathon runners. The present work reports on the physical characteristics of the 392 (310 males, 82 females) starters and 270 (216 males, 54 females) finishers of the 2007 Western States Endurance Run, one of the largest 161-km trail runs in North America. Among the starters, mean (and 25th to 75th percentiles) body mass index (BMI) values were 23.2 (21.6 - 24.6) and 20.6 (19.4 - 21.9) kg · m-2 for the men and women, respectively. Men were significantly taller, heavier and had greater BMI's across all age groups compared with the women. Among the top-5 overall finishers, mean BMI values were 23.2 (range 22.4 - 24.7) for the men and 19.8 (range 17.3 - 21.1) for the women. Average running speed and BMI were negatively correlated for both men (r2 = 0.11, p < 0.0001) and women (r2 = 0.10, p = 0.02). From this analysis, it is concluded that those participating in ultramarathon runs can vary widely in physical characteristics with BMI values that would classify some individuals as underweight and others as overweight. BMI varied considerably even among the top finishers, but lower BMI values were associated with faster running times.